2013
DOI: 10.1158/1541-7786.mcr-12-0395
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental Regulation of BRCA1 Gene Expression by c-Jun and Fra2 in Premalignant Human Ovarian Surface Epithelial Cells

Abstract: Reduced BRCA1 gene expression is common in the sporadic form of ovarian carcinoma. The spread of this highly lethal cancer often begins when tumor cell clusters are shed into the fluid of the abdominopelvic cavity such that they can float freely before seeding distant sites on the peritoneal walls and organs. Thus, the microenvironment that tumor cells find themselves in changes dramatically during these early shedding and floating stages of transperitoneal metastasis. To mimic this microenvironmental change i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
(44 reference statements)
1
12
0
Order By: Relevance
“…The tumor microenvironment is known to affect the regulation of genes, and the expression other tumor suppressor genes, such as BRAC1 and PTEN , is downregulated in the tumor environment. 41 , 42 Here, we showed that FAM49B plays a suppressive role in PDAC, as shFAM49B PDAC cells displayed higher proliferation and invasive ability than their counterparts, both in vitro and in vivo , confirming our initial hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…The tumor microenvironment is known to affect the regulation of genes, and the expression other tumor suppressor genes, such as BRAC1 and PTEN , is downregulated in the tumor environment. 41 , 42 Here, we showed that FAM49B plays a suppressive role in PDAC, as shFAM49B PDAC cells displayed higher proliferation and invasive ability than their counterparts, both in vitro and in vivo , confirming our initial hypothesis.…”
Section: Discussionsupporting
confidence: 78%
“…It gains support from recent report of Mariani et al (2007) who demonstrated amplification and overexpression of c-Jun can block adipocytic differentiation leading to undifferentiated highly aggressive tumors 40 . Zhou et al (2013) also showed that changes in BRCA1 gene expression is regulated by c-Jun and Fra-2 that bind to the CRE element in early stages of ovarian carcinoma that suppress BRCA1 expression in sporadic tumors and promote tumor progression 41 . Together, these findings suggest that selective participation of c-Jun with c-Fos-Fra-2 protein complex of AP-1 plays an important role in maintaining undifferentiated tumor phenotype, aggressiveness and poor prognosis that may lead to drug resistance, treatment failure and disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…The various FOS proteins play key roles in distinct developmental, physiological, and pathological processes [6], but these individual roles and the mechanisms involved are not yet clear. FOSL2 exerts a specific function in bone development [7] and appears to have selective physiological and pathological roles in diverse processes, including photoperiodic regulation [8], cancer [9], and fibrosis [10]. Several previous studies have indicated that FOSL2 plays a key role in the regulation of TGF-β pathway.…”
Section: Introductionmentioning
confidence: 99%